Estimating the quadratic covariation of an asynchronously observed semimartingale with jumps - Markus Bibinger; Mathias Vetter (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2013)
We consider estimation of the quadratic (co)variation of a semimartingale from discrete observations which are irregularly spaced under high-frequency asymptotics. In the univariate setting, results from Jacod (2008) are generalized to the case of irregular observations. In the two-dimensional setup under non-synchronous observations, we derive a stable central limit theorem for the estimator by Hayashi and Yoshida (2005) in the presence of jumps. We reveal how idiosyncratic and simultaneous jumps affect the asymptotic distribution. Observation times generated by Poisson processes are explicitly discussed.
Keywords: G10; C14; 330; asynchronous observations; co-jumps; statistics of semimartingales; quadratic covariation